The child labor situation in the commercial and construction sectors in Bangladesh - Karim, A.H.M Zehadul (University Grants Commission (UGC) of Bangladesh, Agragon, Dhaka, Bangladesh, 2012)
The participation of under-aged children as child labor in multifarious work-activities is a widespread phenomena throughout the world. Although, child labor is legally restricted in many countries of the world, yet the International Labor Organization (ILO) estimated that there were about 40 million children below 15 years of age who were engaged in paid employment in 1985; and in spite of repeated penalties declared by many nations, the number still remained at 34 million until 1988 (see Jomo 1992). A recent ILO survey indicated that 73 million world’s children are employed as an equivalent to 13 per cent of those aged 10 to 14 is another example of this issue (see ILO 1996). As we come to accept the fact that there are millions of under-aged children who are employed as potential labor-force throughout the world, the imposition of laws could not however, control the family employment when people find it an easy means to circumvent the regulations. It is therefore quite likely that the participation of the children from the low income families in both domestic and non-domestic sectors of production will continue to increase in future. And there is no doubt that this sort of patronization of child labor must have some detrimental effect on their schooling and of children’s future socialization process.